The advertising of financial products in the press - Heather Adams (Ibérica, Revista de la Asociación Europea de Lenguas para Fines Específicos, 2007)
Although experts on advertising and the discourse of advertising have traditionally presented a series of features common to all adverts, the incidence of these features depends on a number of factors, including the type of product being promoted, the market being addressed and the media used. This article presents the results obtained from an analysis of a corpus of English print adverts for financial products focussing on lexical, semantic, syntactic and pragmatic aspects. Initial research determined the salient features of this type of advert enabling us subsequently to observe the extent to which they differ from adverts for consumer goods in general. The rapid expansion of this product sector and its advertising over recent decades makes it a particularly interesting area to study, while industry estimates predict that the money spent on advertising in this sector will increase substantially over the next five years, ensuring its relevance as a field of study. This paper, and the material involved, can be useful in itself as a description of a particular discourse, but can also be regarded as a tool to be used in translation, translator training and the teaching of English for specific purposes.